Social protection in humanitarian contexts: Exploring stakeholder views from Tanzania - Roosa Lambin; Winnie C. Muangi; Milla Nyyssölä (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2025)
This working paper examines Tanzania's social protection system amidst growing humanitarian crises driven by climate change, health epidemics, and regional conflicts. It explores the social protection needs experienced in humanitarian settings, the challenges in implementation and expansion of social protection schemes, and the opportunities for future policy reform to move towards shock-responsive systems. The study underscores the importance of integrating humanitarian responses into national social protection frameworks and expanding social protection to informal sector groups. Key recommendations include anticipatory planning, increased domestic financing, strengthened legal frameworks, and leveraging technology and data for emergency preparedness, accurate targeting, and system monitoring. The paper calls for a multistakeholder approach to building a resilient social protection system for vulnerable populations that meets the diverse and evolving needs of Tanzania's population in an era of escalating shocks and polycrises.
Keywords: I38; H53; O55; J46; 330; social protection; humanitarian crises; Tanzania; climate change; health epidemics; vulnerable populations